2009
DOI: 10.4269/ajtmh.2009.81.443
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prednisolone Plus Albendazole with Prednisolone Alone for Treatment of Patients with Eosinophilic Meningitis

Abstract: Corticosteroid and the combination of corticosteroid and antihelminthic drug are safe and beneficial in relieving headaches in patients with eosinophilic meningitis. However, clinical trials comparing the efficacies of these regimens have never been reported. We conducted a prospective, open, randomized, controlled study to compare the efficacy of the combination of prednisolone plus albendazole and prednisolone alone for the treatment of eosinophilic meningitis. Our study had 53 patients in the combined treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 5 publications
1
42
1
Order By: Relevance
“…Chotmongkol et al (24) found that a 2-week course of prednisolone helped relieve the headache, shortened the median time until resolution of headache, and reduced the need for repeated lumbar puncture. They did not find a better treatment effect when combination therapy with prednisolone and albendazole was compared to prednisolone alone (25). We treated the present patient with a 2-week duration of prednisolone and the outcome was good.…”
Section: Discussionmentioning
confidence: 55%
“…Chotmongkol et al (24) found that a 2-week course of prednisolone helped relieve the headache, shortened the median time until resolution of headache, and reduced the need for repeated lumbar puncture. They did not find a better treatment effect when combination therapy with prednisolone and albendazole was compared to prednisolone alone (25). We treated the present patient with a 2-week duration of prednisolone and the outcome was good.…”
Section: Discussionmentioning
confidence: 55%
“…[18][19][20] Treatment is primarily supportive; systemic corticosteroids may decrease symptom duration, but the use of antihelminthic therapy is controversial. 21,22 We previously reported a laboratory-and hospital-based investigation in Hawaii that included case data from January 2001 to February 2005. 23 In that study, we found a cluster of angiostrongyliasis cases that occurred on the island of Hawaii from November 2004 to February 2005.…”
Section: Introductionmentioning
confidence: 99%
“…2,36 However, these drugs are widely used in some countries as they have been shown to relieve symptoms and reduce the extent of the disease in some patients. 31 Our collection and identification of A. cantonensisinfected snails reflected a high prevalence of the parasite in the region. Nearly three decades back, the only reported environmental investigation in Guadeloupe was done for A. costaricensis in rats (R. rattus and in R. norvegicus), which showed a total prevalence of 7.5% in the region.…”
Section: Discussionmentioning
confidence: 95%
“…Corticosteroid therapy was aimed at improving neurologic symptoms by limiting cranial inflammation. 30,31 Cerebral MRI and hematological investigations did not yield any information about the cause of disease. Typical laboratory findings of A. cantonensis can include peripheral hypereosinophilia, increased CSF pressure, increased CSF protein, and a normal or decreased CSF glucose.…”
Section: Discussionmentioning
confidence: 99%